Festejar las fiestas patrias desde una perspectiva cosmopolita. ¿Cómo puede un “ciudadano del mundo” celebrar el “Día de la Independencia”? - Soto Acosta, Willy (2013)
The article analyzes how the celebrationof national festivities in our countriesmay end up in an unbridled nationalismwith all and its dangers whichcould affect not only the citizens but alsothe foreigners living in the country. Thisproblematic situation is targeted specificallyfor Costa Rica, a country that creates anidentity in a contradictory process: isolatingitself and at the same time participating inthe Central American integration process.The essay finishes focusing on the compatibilitybetween being proud of the local identityand being a world citizen, within a vision thatrespects the “otherness of the other”.